2021
DOI: 10.1155/2021/5548968
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine, Guilu Erxian Glue, as Alternative Medicine for Adverse Side Effects of Chemotherapy in Doxorubicin-Treated Cell and Mouse Models

Abstract: Doxorubicin (DOX), a chemotherapeutic drug, often causes many adverse side effects in patients with cancer, such as weight loss, motor disability, blood circulation defects, myelosuppression, myocardial injury, joint degeneration, and bone loss. The Chinese herbal medicine Guilu Erxian Glue (GEG) has been used in the prevention and treatment of osteoarthritis and osteoporosis for hundreds of years, with considerably fewer side effects. We expected that GEG could serve as a protective and beneficial alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Chemical drugs play a predominant role in the clinical treatment of these CSDs due to their rapid effects ( Rodan and Martin, 2000 ; Gordon and Gordon, 2020 ). However, it has been observed that chemical drugs have many adverse effects ( Lien et al, 2021 ). For example, Gupta, et al ( Gupta, et al, 2019 ) reported bisphosphonates are used to treat OP, resulting in adverse reactions such as o oily skin, fluid retention, nausea, long-term toxicity, and even prostate cancer in males; Christian et al ( Christian et al, 2021 ) reported NSAIDs would lead to cardiovascular, renal and gastrointestinal events in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical drugs play a predominant role in the clinical treatment of these CSDs due to their rapid effects ( Rodan and Martin, 2000 ; Gordon and Gordon, 2020 ). However, it has been observed that chemical drugs have many adverse effects ( Lien et al, 2021 ). For example, Gupta, et al ( Gupta, et al, 2019 ) reported bisphosphonates are used to treat OP, resulting in adverse reactions such as o oily skin, fluid retention, nausea, long-term toxicity, and even prostate cancer in males; Christian et al ( Christian et al, 2021 ) reported NSAIDs would lead to cardiovascular, renal and gastrointestinal events in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of GLZ was assessed through a 1,1-diphenyl-2-picrylhydrazyl (DPPH, D9132, Sigma-Aldrich, St. Louis, MO, USA) assay. The DPPH assay method was similar to that used in our previous research [ 21 ]; the DPPH free radical scavenging of the 0.2% GLZ treatment was analyzed using a mixture of DPPH in methanol. The cytotoxicity to Kupffer cells of the 0.2% GLZ treatment was assessed by using a3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, M5655, Sigma-Aldrich Co., St. Louis, MO, USA) assay.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of inflammatory cytokines in Kupffer cells treated with YGW was examined using the enzyme-linked immunosorbent assay (ELISA). Similar to our previous study [ 13 ], purified rat anti-mouse tumor necrosis factor- α (TNF- α ) (88–7324; Invitrogen, Carlsbad, CA, USA) and rat anti-mouse interleukin-1 β (IL-1 β ) (88–7013; Invitrogen) were added to a 96-well microwell plate (Thermo Scientific Nunc, Nunc AS, Copenhagen, Denmark). After the plate was washed three times with PBST buffer, the cell supernatant sample and antibody standard were added.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the protein expression of SOD2, TNF-α, and caspase 3 in the liver tissue was assessed through Western blotting. Similar to our previous study [13][14][15][16], we homogenized and quantified liver tissues and then transferred them onto polyvinylidene difluoride membranes (GE Healthcare Life Sciences, Barrington, IL, USA). Antibodies against β-actin ( ermo Fisher Scientific), SOD2, TNF-α, and caspase 3 (Cell Signaling Technology) were detected, visualized, and quantified using ImageJ analysis software (version 1.48t, NIH, Wayne Rasband, Washington DC, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%